Self-transcending meditation is good for mental health: why this should be the case. (3rd May 2016) - Hankey, Alex; Shetkar, Rashmi
Abstract: A simple theory of health has recently been proposed: while poor quality regulation corresponds to poor quality health so that improving regulation should improve health, optimal regulation optimizes function and optimizes health. Examining the term 'optimal regulation' in biological systems leads to a straightforward definition in terms of 'criticality' in complexity biology, a concept that seems to apply universally throughout biology. Criticality maximizes information processing and sensitivity of response to external stimuli, and for these reasons may be held to optimize regulation. In this way a definition of health has been given in terms of regulation, a scientific concept, which ties into detailed properties of complex systems, including brain cortices, and mental health. Models of experience and meditation built on complexity also point to criticality: it represents the condition making self-awareness possible, and is strengthened by meditation practices leading to the state of pure consciousness—the content-free state of mind in deep meditation. From this it follows that healthy function of the brain cortex, its sensitivity, y and consistency of response to external challenges should improve by practicing techniques leading to content-free awareness—transcending the original focus introduced during practice. Evidence for this is reviewed.